Pengembangan UMKM â€œBeliaâ€ melalui E-Commerce di Kota Bandung - Afriantari, Rini; Taufik, Taufik (Society : Jurnal Pengabdian Masyarakat, 2024)
The development of the Industrial Revolution 4.0 has had a significant impact, one of which can be seen in the practice of e-commerce, a buying and selling transaction activity that utilizes the internet system, especially on gadget devices. In this context, UMKM Belia, a cake business operating in the Santosa Asih Jaya Complex, Cipamokolan Village, Rancasari District, Bandung, West Java, is the target partner to face this change. A review of the priority problems of MSMEs â€œBeliaâ€ reveals a focus on two main aspects: financial management and marketing strategy. In order to overcome these challenges, solution steps in the marketing sector can be taken by developing an online strategy through social media platforms such as Instagram. Besides that, creating exciting content through blogging can be an effective means of reaching potential consumers. Furthermore, young MSMEs can utilize virtual stores on marketplace platforms such as Grab Food to expand their sales reach. It provides opportunities for further growth and opens a broader sales scope. As for increasing transaction capabilities via e-commerce, using M-banking transfer methods, QRIS, and other digital payment solutions can be a progressive step to adapt to rapidly developing industry trends.